Estradiol mediates sex differences in aversion-resistant alcohol intake - Arnold, Miranda E.; Decker Ramirez, Ellie B.; Beugelsdyk, Lauren A.; Siano Kuzolitz, M. Vitória; Jiang, Qiuyun; Schank, Jesse R. (Frontiers in Neuroscience, 2023)
Introduction Alcohol consumption despite negative consequences is a core symptom of alcohol use disorder. This can be modeled in mice by pairing aversive stimuli with alcohol consumption, such as adding the bitter tastant quinine to the alcohol solution. If an animal continues to drink alcohol despite such negative stimuli, this is typically considered aversion-resistant, or inflexible, drinking behavior. Previous studies in our lab have found that females are more aversion-resistant than males in that they tolerate higher concentrations of quinine before they suppress their alcohol intake. Interestingly, we did not observe any differences in intake across the estrous cycle. In regards to neuronal activation patterns during quinine-alcohol intake, we have found that male mice show higher levels of activation in the ventromedial prefrontal cortex and posterior insular cortex, while females show higher levels of activation in the ventral tegmental area. Methods In the experiments presented here, we conducted ovariectomies to further examine the role of circulating sex hormones in aversion-resistant alcohol intake and neuronal activation patterns. Furthermore, we used hormonal addback of estradiol or progesterone to determine which ovarian sex hormone mediates aversion-resistant consumption. Results We found that ovariectomy reduced quinine-adulterated alcohol intake, demonstrating that circulating sex hormones play a role in this behavior. We also observed reduced neuronal activation in the VTA of ovariectomized mice compared to sham females, and that estradiol supplementation reversed the effect of ovariectomy on quinine-alcohol intake. Discussion Taken together with our prior data, these findings suggest that circulating estradiol contributes to the expression of aversion-resistant alcohol intake and neuronal activity in the VTA. However, since this behavior is not affected by the estrous cycle, we believe this is due to a threshold level of this hormone, as opposed to fluctuations that occur across the estrous cycle.